Influence of Trade credit on the Growth of Small and Medium Size Manufacturing Enterprises in Rwanda - Rubunda, Emmaboles; Namusonge, Gregory. S.; Oluoch, Oluoch (Machakos University Press, 2021)
The purpose of this study was to analyze the influence of trade credit on the growth of manufacturing SMEs in Rwanda. To achieve the objective, the study used a mixed research approach involving both qualitative and quantitative methods. The target population of this study consisted of all the 868 small and medium manufacturing enterprises registered with Rwanda Development Board from which a sample of 273 firms was taken by way of stratified random sampling technique. Close-ended questionnaires were used in data collection. The data collected was analyzed using Statistical Package for Social Science 22 to generate descriptive statistics including percentages, frequency tables and mean scores. Multiple regression analysis was used to explore the relationship between Trade credit finance structure and the growth of small and medium size manufacturing enterprises in Rwanda. R2 was deployed to measure the extent of the goodness fit of the regression model. The findings from the study show beta values of (β=0.082, p=0.047) for trade credit finance. Hence, trade credit influences the growth of small and medium manufacturing enterprise in Rwanda. Among recommendations, the management of the SMEs should learn how to use account receivables and account payable to fully take advantage of trade credit finance. This will ensure SMEs continue producing or manufacturing during time of low liquidity and financial constraints.
Keywords: Trade credit; Small and Medium Size Manufacturing Enterprises; Rwanda